Persepsi Pendidikan Anak Usia Dini Orang Tua Daerah Pesisir Suku Bajo Kabupaten Wakatobi - Waode Heni Fitriani; Waode Ekadayanti (Jurnal Sultra Elementary School, 2022)
Based on the results of the study, it can be concluded that parents’ perceptions of education in the coastal area of the Bajo tribe in Sama Bahari Village have changed compared to previous years. Over time, there has been a growing awareness regarding the meaning, importance, function, and goals of early childhood education, as well as parents’ expectations for their children’s education. Parents perceive early childhood education as a form of learning provided to children under the age of seven before entering elementary school, where they can learn various basic skills such as reading, counting, writing, and singing. Parents hope that through this education, their children will become intelligent, successful individuals who can make them proud. However, some parents still believe that education should begin only when the child reaches seven years old and is ready to enter elementary school, mainly due to financial constraints.